2021
DOI: 10.1108/jfm-02-2021-0025
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative system dynamics approach to modeling the causes and effects of design deficiencies in construction projects

Abstract: Purpose Poor quality of design documents and Design Deficiencies (DDs) are critical factors that can potentially cause time and cost overrun and lead to project failure. Despite the importance of this issue, few studies have been conducted to explore the underlying relations among the causes and effects of DDs, and it is not clear how they exert influence on each other. However, it is imperative to have a clear understanding of their interrelationships so as to devise intervention strategies. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…They represent the impact of poor design documentation quality on project delivery. However, earlier researches indicated that poor design documentation quality may result in project delays; generation of rework; project abandonment; structural collapse; (Agbaxode et al, 2021a;Shoar and Payan, 2021;Abdallah et al, 2018;Hughes and Thorpe, 2014;Sunday and Afolarin, 2013) and shoddy works (Philips-Ryder et al, 2013;Lopez et al, 2010). This is consistent with the results of this study.…”
Section: Impacts Of Poor-quality Design Documentation On Project Deli...supporting
confidence: 92%
See 2 more Smart Citations
“…They represent the impact of poor design documentation quality on project delivery. However, earlier researches indicated that poor design documentation quality may result in project delays; generation of rework; project abandonment; structural collapse; (Agbaxode et al, 2021a;Shoar and Payan, 2021;Abdallah et al, 2018;Hughes and Thorpe, 2014;Sunday and Afolarin, 2013) and shoddy works (Philips-Ryder et al, 2013;Lopez et al, 2010). This is consistent with the results of this study.…”
Section: Impacts Of Poor-quality Design Documentation On Project Deli...supporting
confidence: 92%
“…All these factors had RII values between 0.82 -0.90 which falls within 0.8≤RII≤1 indicating high importance. This is consistent with earlier researches which asserts that poor design documentation quality may lead to project cost overrun (Shoar and Payan, 2021;Hughes and Thorpe, 2014;Ramabodu and Verster, 2013;Love et al, 2010;Mohammed, 2007); variation costs (Philips-Ryder et al, 2013;Love et al, 2010); and dissatisfaction by project owners (Sunday and Afolarin, 2013).…”
Section: Impacts Of Poor-quality Design Documentation On Project Deli...supporting
confidence: 92%
See 1 more Smart Citation
“…It is believed that the construction industry significantly contributes to the economy of both developed and developing countries [1][2][3]. Within the urban contexts, this industry especially lends its prosperity to high-rise buildings, among other project types, as they absorb considerable investments from both public and private sectors and play a crucial role in the development of a country [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since the total number of contractor companies in Iran is more than the number of consulting companies and client representatives, thus, the like sample size for the client and design firms' representatives was considered. Due to the differences between practitioners with regard to their experience and expertise, the weights of experts are not equal (Shoar and Payan, 2021). Therefore, the weighting factors of experts were determined based on their experience index scores.…”
Section: Network Analysis Through Sna and Questionnaire Designmentioning
confidence: 99%